2022
DOI: 10.1111/evj.13571
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cryptosporidium spp. in Horses from communities of the Mapuche native people, Araucanía Region, Chile

Abstract: Background:There are no studies of potential zoonotic diseases in Mapuche communities' horses. Objectives:The objective of this study was to determine the prevalence of Cryptosporidium in horses of the Mapuche communities. Study design:This was a cross-sectional study.Methods: Faecal samples from 100 randomly selected horses (n = 100) were taken from rural Mapuche communities from four municipalities from the Araucanía Region.These samples were processed with the modified Ziehl-Neelsen staining technique and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(60 reference statements)
3
5
0
1
Order By: Relevance
“…The sex of the horse was not also associated with Cryptosporidium spp. infection in the current study which is consistent with published research(Tuemmers, et al 2022). In the current study, we attempted to extract DNA and amplify 18S rRNA genes using PCR from a random subset of positive samples but none of the PCR reactions yielded positive results.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…The sex of the horse was not also associated with Cryptosporidium spp. infection in the current study which is consistent with published research(Tuemmers, et al 2022). In the current study, we attempted to extract DNA and amplify 18S rRNA genes using PCR from a random subset of positive samples but none of the PCR reactions yielded positive results.…”
supporting
confidence: 94%
“…Another recent study from Chile that investigated Cryptosporidium spp. infection prevalence in 100 adult horses using microscopy reported greater prevalence of 67%(Tuemmers et al 2022). Earlier studies of the prevalence of Cryptosporidium spp.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Efectivamente, Sudamérica tiene poblaciones de personas indígenas quienes tienen caballos como animales de trabajo y viven en lugares remotos llevando una relación cercana al medio ambiente que los rodea. Estas condiciones hacen que las enfermedades zoonóticas sean de preocupación significativa, ese riesgo fue destacado por Tuemmers et al (2023), 2 quien identifico una prevalencia de 67% de Cryptosporidium spp. en las heces de caballos de trabajo en la comunidades rurales Mapuches en la Región de la Araucanía en Chile.…”
Section: Discussionunclassified
“…Indeed, South America has populations of indigenous people who keep horses as working animals, and live in remote locations with very close relationships to their surrounding environment. These conditions make zoonotic diseases a significant concern, the risk of which was highlighted by Tuemmers et al, 2 who identified a 67% prevalence of Cryptosporidium spp. in the faeces of working horses of the rural Mapuche communities in the Araucania region of Chile.…”
Section: A South American Perspective On Infectious Diseases and Donk...mentioning
confidence: 99%